2020
DOI: 10.1002/chem.202001718
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Turn‐On BODIPY‐Peptide Photosensitizers for Tailored Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) leads to cancer remission via the production of cytotoxic species under photosensitizer (PS) irradiation. However,c oncomitantd amage and dark toxicity can both hinder itsu se. With this in mind, we have implemented av ersatile peptide-based platform of bioorthogonally activatable BODIPY-tetrazine PSs. Confocal microscopy and phototoxicity studies demonstrated that the incorporation of the PS, as ab ifunctionalm odule, into a peptidee nabled spatiala nd conditional controlo fs inglet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 94 publications
0
21
0
1
Order By: Relevance
“…Therefore, 130 could rapidly induce over 95% HeLa cell death with an IC 50 value of 2.0 μM in the presence of transcyclooctene and light irradiation. In addition, Vázquez et al reported a peptide-based platform of bioorthogonally activatable tetrazine-BODIPY PSs with high photocytotoxicity (IC 50 = 0.096 μM) …”
Section: Representative Strategies For Efficient Photosensitizer Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 130 could rapidly induce over 95% HeLa cell death with an IC 50 value of 2.0 μM in the presence of transcyclooctene and light irradiation. In addition, Vázquez et al reported a peptide-based platform of bioorthogonally activatable tetrazine-BODIPY PSs with high photocytotoxicity (IC 50 = 0.096 μM) …”
Section: Representative Strategies For Efficient Photosensitizer Designmentioning
confidence: 99%
“…In addition, Vaźquez et al reported a peptide-based platform of bioorthogonally activatable tetrazine-BODIPY PSs with high photocytotoxicity (IC 50 = 0.096 μM). 281 Similarly, Ng et al designed another BODIPY-tetrazine conjugate-based PS (131) for site-specific PDT action (Figure 63a). 282 To achieve active targeting, 131-TCO was prepared via the conjugation of TCO with a biotin moiety, which has been widely employed in cancer therapy and theranostics because its receptor is overexpressed on the membrane of cancer cells.…”
Section: Activatable Pssmentioning
confidence: 99%
“…The borondipyrromethene (BODIPY) scaffold is an attractive fluorophore for the development of imaging probes due to its excellent photophysical properties. [16] Current approaches for synthesizing BODIPY-peptide conjugates include classical CuAAC [17] and SPAAC [18] methods using pre-functionalised intermediates, total solid-phase approaches for in situ dipyrrin construction on N-terminal/Lys sites [19] and the use of BODIPYbearing FlAAs, [12a] with the latter enabling site-selective fluorophore incorporation without disrupting the native biomolecular properties of peptides. Among the different BODIPY structures reported for the construction of FlAAs, the fluorogenic Trp-BODIPY (4, Figure 1a) stands out for its utility in wash-free imaging of biological systems.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the IEDDA-based activatable photodynamic strategies could be a useful tool for PDT. Next, Vázquez and coworkers developed a bioorthogonal turn-on peptide PS (Tz-C(2I-BODIPY)-PEPTIDE) [ 119 ]. Unlike the previous BODIPY/Tz photosensitizer, the tetrazine and BODIPY moieties were separately integrated into a cell membrane-targeted peptide.…”
Section: Applicationsmentioning
confidence: 99%